If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 8 + 7x = 6 Reorder the terms: 8 + -5x + 7x = 6 Combine like terms: -5x + 7x = 2x 8 + 2x = 6 Solving 8 + 2x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = 6 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 6 + -8 2x = 6 + -8 Combine like terms: 6 + -8 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 2(4f+2g)2=2f(4+2g) | | 3=3tx-5x | | cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x | | 4.9-5.2=4.7 | | x+x+x+2=3x+2 | | 0=80x-x | | 7x-6=3x+54 | | 4d+6+2d=6(d+6) | | -6x-12+8x-21=-6 | | x*1.012048193=84 | | -3x+11+5x+17=4 | | (4x-5)(2x+1)=0 | | 2(3d+3)=4d+6+2d |